Adoption of Artificial Insemination Among Large Ruminants in Arid Western Rajasthan, India - Hajong, Dipika; Patel, A. K.; Pramendra,; Manjunatha, B. L.; Kachhawaha, S.; Tewari, Pratibha (Indian Journal of Extension Education, 2022)
This study estimated the adoption rate of Artificial Insemination (AI) among large ruminants based on primary data collected from 200 farm households in Jodhpur district from 2019 to 2022. The composition of cow and buffalo population was 74 and 26 per cent in the study villages. 56 per cent farmers in cows and 13 per cent in buffaloes adopted AI with a success rate of conception after first insemination of 31 per cent in cows and 22 per cent in buffaloes. AI cost ranged from Rs. 400-800/- and Rs. 500-1000/- per insemination in cows and buffaloes respectively. Breeding cost through pedigreed bull was comparable to insemination in both cows and buffaloes. Subsistence mode of livestock rearing and natural grazing on community pastures were the main reasons for low adoption rate of AI. Farmers ensured that their buffaloes were sired only through pedigreed bulls. Since, pedigreed bulls were not available in all villages, their availability in villages or at the selected farmers on payment basis is required for genetic improvement of cattle.
Keywords: Arid region; Artificial insemination; Cow; Buffalo; Farming system; Subsistence agriculture